Lightweight reinforced concrete for assembled buildings and preparation method thereof

Through the combination of modified ceramite and reinforced fibers, a lightweight reinforced concrete suitable for prefabricated buildings was prepared, which solved the problem of difficulty in taking into account early strength and later strength, and achieved the goal of improving compressive, tensile, and flexural resistance and lightweight.

CN119306452BActive Publication Date: 2025-03-21ZHEJIANG HUIJING CONSTR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411864702.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing prefabricated building concrete components have shortcomings in taking into account compression, tensile, flexural properties and lightweight, and it is difficult to take into account both early and later strength.

Method used

By modifying the light clay aggregate, a lightweight reinforced concrete for prefabricated buildings is prepared. The silicate cement grading control and blending materials are used to form a two-layer modified interface on the surface of the clay, and reinforcing fibers are added to improve the overall performance of the concrete.

Benefits of technology

The early strength improvement of concrete has been achieved, the mold removal cycle has been shortened, the production efficiency has been improved, and the compressive and flexural properties have been enhanced, ensuring the lightweight and high toughness of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of functional building materials, and discloses a lightweight reinforced concrete for prefabricated buildings and a preparation method thereof. The lightweight reinforced concrete comprises the following raw material components by weight: 320-340 parts of PO 42.5 ordinary Portland cement, PO 52.5 100-120 parts of ordinary Portland cement, 30-50 parts of fly ash, 20-30 parts of silica fume, 5-10 parts of metakaolin, 200-220 parts of fine aggregate, 50-100 parts of fly ash floating beads, 600-700 parts of modified lightweight coarse aggregate, 5-7 parts of polycarboxylic acid high-efficiency water reducer, 15-20 parts of reinforcing fiber, and 145-160 parts of water; the surface of the modified lightweight coarse aggregate is a two-layer modified interface, including a first interface with elastic function and a second interface with compactness, which effectively prevents the concrete from being crushed; through the control of the particle size grading of Portland cement and the combination of admixtures, a stronger hydration product is formed with better self-compactness, thereby enhancing the compression and flexural properties of the concrete; the early strength of the concrete is improved, and the demolding cycle of prefabricated concrete components of prefabricated buildings is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional building materials, and in particular relates to functional concrete building materials, and specifically relates to lightweight reinforced concrete for prefabricated buildings and a preparation method thereof. Background Art

[0002] Prefabricated buildings are buildings that are assembled on site by making prefabricated building components according to standards on a factory assembly line. Prefabricated buildings are in line with the development trend of green buildings because they reduce the impact of the construction site on the environment, have stable and controllable building quality, high construction efficiency, short construction period, save materials, and reduce construction waste.

[0003] With the development of prefabricated buildings, there are currently three main structural forms of prefabricated buildings, namely prefabricated concrete structures (PC), prefabricated steel structures (PS) and prefabricated wooden structures. Among them, prefabricated concrete structures are easy to obtain raw materials, can use industrial waste such as slag and fly ash, have low costs, stable performance, good durability, and are easy to shape. They have become the largest proportion of prefabricated building components. At present, prefabricated building concrete components (PC) can be prefabricated in factories, such as prefabricated columns, prefabricated beams, prefabricated exterior wall panels, prefabricated partitions, prefabricated floor slabs, prefabricated air-conditioning panels, prefabricated stairs, prefabricated balconies, etc. Since prefabricated buildings are an industrialized and intensive construction method, the performance requirements for concrete materials are more stringent.

[0004] On the one hand, when assembling buildings, concrete components are prefabricated and embedded with steel sleeves, steel anchors, welding, bolts and other connections. The tensile force is transmitted by connecting bars and embedded parts welding, which have the ability to resist stretching and shearing. Therefore, the strength requirements of the concrete structure itself are relatively high. In addition, the mechanical work requirements such as transportation and installation require the concrete structure to have good strength and toughness.

[0005] On the other hand, the concrete components of prefabricated buildings are heavier, usually with a density of more than 2300kg / m 3, increasing the cost of transportation and hoisting. Therefore, how to balance the compressive performance, tensile performance, flexural performance and lightweight of prefabricated building concrete becomes the key. In order to achieve the lightweight of prefabricated building concrete components, the existing technology mainly reduces the density of concrete by using lightweight aggregates such as ceramsite. However, when ceramsite is used to replace the gravel aggregate in concrete, due to the presence of more voids in ceramsite, its own strength is lower than that of sand and gravel, and it is brittle and easily fractured, resulting in low strength of prefabricated concrete, which limits the development of high-strength lightweight concrete. It is only suitable for use in non-load-bearing wall materials such as partitions. Moreover, when prefabricating and assembling building concrete, the use of lightweight ceramsite causes excessive adhesion and condensation of cement slurry due to the adsorption of voids on the surface of ceramsite, and the water-cement ratio is difficult to control. During pumping, a certain resistance will be generated in the pipeline, affecting the pumping stability.

[0006] Furthermore, when prefabricated building concrete components are produced in factories, not only high strength and high toughness of concrete are required, but also high early strength of concrete is required, so as to improve the turnover rate of the casting platform, reduce the amount of mold input, and improve production efficiency. According to the current technical practice of concrete precast parts production, ordinary concrete components are required to reach a strength of 15MPa after 8 hours of casting for demolding and lifting; for prestressed concrete components, the strength is required to reach 20MPa after 8 hours of casting for demolding and lifting. Therefore, when designing the concrete formula, it is necessary to comprehensively consider the early strength and the later strength.

[0007] Therefore, the development of concrete that is lightweight, has good workability, stable pumping, and has high compressive toughness has become an urgent need for the development of prefabricated buildings. Summary of the invention

[0008] The present invention proposes a lightweight reinforced concrete for prefabricated buildings, which achieves the lightweighting of prefabricated building concrete by modifying ceramsite lightweight aggregate, while overcoming the defects of existing lightweight concrete in terms of low compressive strength, tensile strength and toughness, and meeting the use requirements of prefabricated building concrete; further, a preparation method of the lightweight reinforced concrete for prefabricated buildings is provided.

[0009] In order to achieve the above technical objectives, the present invention provides the following specific technical solutions:

[0010] First, a lightweight reinforced concrete for prefabricated buildings is provided, wherein the lightweight reinforced concrete comprises raw material components in parts by weight: 320-340 parts of PO 42.5 ordinary Portland cement, 100-120 parts of PO 52.5 ordinary Portland cement, 30-50 parts of fly ash, 20-30 parts of silica fume, 5-10 parts of metakaolin, 200-220 parts of fine aggregate, 50-100 parts of fly ash floating beads, 600-700 parts of modified lightweight coarse aggregate, 5-7 parts of polycarboxylate high-efficiency water reducing agent, 15-20 parts of reinforcing fiber, and 145-160 parts of water; wherein:

[0011] The PO 42.5 ordinary Portland cement is ground to a D80 particle size of 5-15 μm;

[0012] The particle size of the PO 52.5 ordinary Portland cement D80 is 30-45 μm;

[0013] The surface of the modified lightweight coarse aggregate is a two-layer modified interface, including a first interface with elasticity and a second interface with compactness; the modified lightweight coarse aggregate is prepared by the following method:

[0014] (1) Add silicate cement, ultrafine glass powder, water-based polyurethane dispersion and silica sol in a mass ratio of 10: (10-15): (5-10): (0.8-1) into a stirring container, add water and stir until a thin elastic slurry with a fluidity of 200-250 mm is obtained, then add ceramsite made from high-alumina fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, sieve out the ceramsite with a sieve, and dry naturally for more than 24 hours, so that a first elastic interface is formed on the surface of the ceramsite;

[0015] (2) adding silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate into a mixing container in a mass ratio of 10: (25-30): (1-2): (2-3), adding water and stirring until a thin slurry with a fluidity of 130-150 mm is obtained, and then adding the ceramsite adsorbed on the first interface into the mixing container and stirring slowly to allow the slurry to adhere to the surface of the ceramsite to form a second interface;

[0016] (3) Use a cylindrical filter to automatically screen out the slurry-covered expanded clay, and after natural solidification for 3 hours, send it into a rotating drum to separate the bonded expanded clay by rotation. After 12 hours, pile it on the site and water it for natural curing. Wet it once every 3 days and cure it for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm.

[0017] Further preferably, the weight ratio of the PO 42.5 ordinary Portland cement to the PO 52.5 ordinary Portland cement is 3:1; when the cement particle size is fine or the specific surface area is large, the interface for hydration reaction with water is larger, the hydration reaction rate is faster, and the early strength is high, which can reasonably shorten the demolding period of prefabricated concrete components of prefabricated buildings and improve the production effect; through reasonable cement grading, small-particle-size PO 42.5 ordinary Portland cement is used to accelerate hydration and improve early strength; at the same time, large-particle-size high-grade PO 52.5 ordinary Portland cement is used to promote later hydration and hardening, thereby improving the later strength of concrete components.

[0018] Further preferably, the water-cement ratio of the lightweight reinforced concrete is controlled at 0.32-0.35. Although lower water-cement ratio can increase the strength of concrete, the water-cement ratio cannot be controlled too low, otherwise it is easy to block the pipe and affect the pumping and distribution of concrete.

[0019] Further preferably, the particle size of the fly ash D80 is less than 10 μm.

[0020] Further preferably, the particle size of the silica fume D80 is less than 3 μm; as an ultrafine spherical powder, silica fume can effectively enhance the rheological effect of concrete, promote the lubrication of concrete, and improve the uniformity and stability of factory-cast assembled concrete components; furthermore, ultrafine silica fume can fully fill the pores between cement particles, significantly reduce the porosity in cement slurry, and form a stronger hydration product, thereby enhancing the compression resistance, flexural resistance and other properties of concrete.

[0021] The best effect is that fly ash and silica fume can improve the flow and uniform distribution of glass fiber, which is significant for improving the overall strength of concrete. However, it is not advisable to use too much fly ash and silica fume, as too much fly ash and silica fume will affect the early strength of concrete.

[0022] Further preferably, the particle size of the metakaolin is less than 10 μm; particularly preferably, the metakaolin has a particle size less than 1 μm; the finer the metakaolin particles, the better the activity, which can effectively promote the secondary reaction of high-alkali calcium silicate in concrete to generate low-alkali hydrated calcium silicate, thereby enhancing the strength of concrete.

[0023] Further preferably, the fine aggregate is a mixture of medium sand with a modulus of 2.3-3.0 and fine sand with a modulus of 1.6-2.2 in a mass ratio of 3:1; the mud content of the fine aggregate is less than 1%.

[0024] More preferably, the particle size of the fly ash floating beads is 100-200 μm, and the bulk density is 720-750 kg / m 3 .

[0025] Further preferably, the reinforcing fiber is a fiber with an elastic modulus higher than that of the cement matrix; such as at least one of alkali-resistant chopped glass fiber, asbestos, mineral wool, and steel fiber; particularly preferably, alkali-resistant chopped glass fiber with a fiber diameter of 13-60 μm and a fiber length of 15-20 mm; alkali-resistant chopped glass fiber has the characteristics of light weight and high strength, and has good dispersion and mixing properties with the concrete system, and can form a three-dimensional randomly distributed network structure in the concrete, which can effectively prevent the expansion of microcracks inside the concrete, thereby improving the tensile properties, flexural properties and crack resistance of the concrete.

[0026] Further preferably, the silicate cement used to prepare the modified lightweight coarse aggregate is at least one of PI 52.5, PI 52.5R, PI 62.5, and PI 62.5R; the cement with high early strength and high late hardness promotes the increase of compressive strength of ceramsite after slurry hanging.

[0027] More preferably, the ultrafine glass powder used to prepare the modified lightweight coarse aggregate is glass powder with a particle size of less than 20 μm; the glass powder is a fine powder mainly composed of silicon dioxide and aluminum oxide made by grinding waste glass products.

[0028] Further preferably, the silica sol used to prepare the modified lightweight coarse aggregate has a silica content of 30-40%; the nano-dispersed silica is dispersed in the cement slurry, combines with the calcium ions in the cement to form calcium silicate compounds, which penetrate and fill the micropores of the ceramsite to increase the strength of the ceramsite.

[0029] Further preferably, the aqueous polyurethane dispersion used to prepare the modified lightweight coarse aggregate is selected from one of anionic aliphatic polyurethane dispersion and anionic aromatic polyurethane dispersion; the anionic aromatic polyurethane dispersion with a solid content of 35-40% is particularly preferred; it has excellent leveling and elasticity, and cooperates with silicate cement, ultrafine glass powder, and silica sol to penetrate and fill the gaps and through cracks on the surface of ceramsite, promote the first interface layer formed by ceramsite to have good toughness and strength, enhance the strength of ceramsite and the density of through holes, increase the anti-fracturing performance, and meet the use of high-strength concrete.

[0030] Further preferably, the particle size of the basalt fine sand used to prepare the modified lightweight coarse aggregate is in the range of 0.1-0.2 mm.

[0031] Further preferably, the magnesium oxide used to prepare the modified lightweight coarse aggregate is a medium powder with a particle size of 10-100 μm.

[0032] Further preferably, amorphous calcium aluminate with a particle size of 10-20 μm is used to prepare the modified lightweight coarse aggregate; on the one hand, amorphous calcium aluminate accelerates the coagulation of mortar and quickly processes expanded clay; on the other hand, amorphous calcium aluminate cooperates with magnesium oxide to promote the formation of a dense gel at the second interface of the expanded clay, and this gel is hydrated to form a relatively stable crystalline product, making the second interface of the expanded clay denser and increasing the compressive strength of the expanded clay.

[0033] Furthermore, the present invention provides a method for preparing the above-mentioned lightweight reinforced concrete for prefabricated buildings, and the specific preparation method is as follows:

[0034] S101. Add silicate cement, ultrafine glass powder, water-based polyurethane dispersion, and silica sol into a stirring container in a mass ratio of 10: (10-15): (5-10): (0.8-1), add water and stir to adjust the fluidity to a thin elastic slurry in the range of 200-250 mm, then add ceramsite made from high-aluminum fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, sieve out the ceramsite with a sieve, and dry it naturally for more than 24 hours, so that a first elastic interface is formed on the surface of the ceramsite;

[0035] S102. Add silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate in a mass ratio of 10: (25-30): (1-2): (2-3) into a stirring container, add water and stir until a thin slurry with a fluidity of 130-150 mm is obtained, and then add the ceramsite adsorbed on the first interface into the stirring container and stir slowly to allow the slurry to adhere to the surface of the ceramsite to form a second interface;

[0036] S103. Use a cylindrical filter to automatically screen out the slurry-hanging ceramsite, and after natural solidification for 3 hours, send it into a rotating drum, separate the bonded ceramsite by rotation, and pile it on the site for natural curing after 12 hours. Wet it once every 3 days for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm;

[0037] S201. Add PO 42.5 ordinary Portland cement, PO 52.5 ordinary Portland cement, fly ash, silica fume, metakaolin, and fine aggregate into a horizontal stirring device and stir for 3-5 minutes to obtain a dry mix;

[0038] S301. Add polycarboxylic acid high-efficiency water reducing agent and water to the dry mix and stir for 2-3 minutes to form a slurry. Then add fly ash floating beads, modified lightweight coarse aggregate and reinforcing fiber and stir for 3-5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0039] The fluidity described in steps S101 and S102 refers to the test method for mortar fluidity involved in standard JC / T 985-2017 (cement-based self-leveling mortar for floor use) to quickly detect the slurry fluidity performance, and the fluidity is the diameter of the mortar spread on the flat surface in 4 minutes. By reasonably controlling the slurry fluidity, it is ensured that the slurry is evenly attached to the surface and gaps of the ceramsite to penetrate and repair the through gaps of the ceramsite.

[0040] When prefabricating concrete components for assembled buildings, the concrete is transported to the PC production line, and according to the design requirements, bolts or connecting rods are embedded, the concrete is poured by a concrete placing machine, the flow mold table is vibrated, leveled, initially cured, and demolded to obtain lightweight prefabricated concrete components for assembled buildings.

[0041] The excellent effects of the present invention are embodied in:

[0042] 1. The present invention improves the early strength of concrete by adjusting the grading of silicate cement and combining admixtures, shortens the demolding period of prefabricated concrete components of assembled buildings, and improves production effects; at the same time, the admixture can fully fill the pores between cement particles to form a more solid hydration product with better self-compactness, thereby enhancing the compression and flexural properties of concrete and improving the later strength growth of concrete components.

[0043] 2. The present invention forms two layers of modified interfaces on the surface of lightweight coarse aggregate. The first interface fills the voids and cracks on the surface of ceramsite through negative pressure penetration and hardens, thereby improving the compressive strength and elasticity of ceramsite and effectively preventing the concrete from being crushed. The second interface uses amorphous calcium aluminate and magnesium oxide to improve the flexural and compressive strength of cement mortar after hydration, making the second interface of ceramsite denser and increasing the compressive strength of ceramsite.

[0044] 3. The present invention uses reinforcing fibers and synergistically modified elastic ceramsite to effectively prevent the expansion of micro cracks inside concrete and improve the tensile and flexural properties of concrete.

[0045] 4. The raw materials required for the manufacturing of the present invention are all conventional and easily purchased raw materials. The prepared concrete is low-carbon and environmentally friendly, has a high slump when used, good workability, stable pumping, and is easy to evenly pump and distribute in the factory to prepare concrete precast parts, which is suitable for the production control requirements of assembled building concrete components. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The specifications of the raw materials used are as follows:

[0048] Water-based polyurethane dispersion: provided by Hefei Huayue New Material Technology Co., Ltd., model PU-600R, anionic aromatic polyurethane dispersion, solid content 35%.

[0049] Silica sol: provided by Guangdong Ke Ning Technology Co., Ltd., model JD-120, silica particle size 110-130nm, solid content 40%.

[0050] Ultrafine glass powder: particle size less than 20μm.

[0051] Basalt fine sand: particle size is 0.1-0.2mm.

[0052] Magnesium oxide: medium powder with particle size distribution of 10-100μm.

[0053] Amorphous calcium aluminate: particle size is 10-20μm.

[0054] PO 42.5 Ordinary Portland Cement: Grind to a D80 particle size of 5-15μm.

[0055] PO 52.5 Ordinary Portland Cement: The particle size of D80 is 30-45μm.

[0056] Fly ash: The particle size of D80 is less than 10μm.

[0057] ‌Silica fume: The particle size of D80 is less than 3μm.

[0058] Metakaolin: particle size less than 1μm.

[0059] Polycarboxylic acid high-efficiency water reducing agent: provided by Zhejiang Yuxuan New Materials Co., Ltd., model is PC-1005.

[0060] Fly ash floating beads: particle size is 100-200μm, bulk density is 750kg / m 3 .

[0061] Alkali-resistant chopped glass fiber: fiber diameter is 19μm, fiber length is 20mm, elastic modulus is 75GPa.

[0062] Example 1

[0063] S101. Add PI 52.5 silicate cement, ultrafine glass powder, water-based polyurethane dispersion, and silica sol into a stirring container in a mass ratio of 10:15:5:0.8, add water and stir until a thin elastic slurry with a fluidity of 200 mm is obtained, then add ceramsite made from high-aluminum fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure. Treat for 120 seconds, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, and sieve out the ceramsite with a sieve, and dry it naturally for more than 24 hours. During the natural drying, rotate the storage barrel once every 2 hours, and each rotation time is 5 minutes to prevent the ceramsite from sticking; so that a first elastic interface is formed on the surface of the ceramsite;

[0064] S102. PI 52.5R silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate are added to a stirring container in a mass ratio of 10:25:1:3, and water is added to stir until a thin slurry with a fluidity of 150 mm is obtained. Then, the ceramsite adsorbed on the first interface is added to the stirring container, and slowly stirred to allow the slurry to hang on the surface of the ceramsite to form a second interface.

[0065] S103. Use a cylindrical filter to automatically screen out the slurry-hanging ceramsite, and after natural solidification for 3 hours, send it into a rotating drum, separate the bonded ceramsite by rotation, and pile it on the site for natural curing after 12 hours. Wet it once every 3 days for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm;

[0066] S201. According to parts by weight, 320 parts of PO 42.5 ordinary Portland cement, 120 parts of PO 52.5 ordinary Portland cement, 30 parts of fly ash, 30 parts of silica fume, 5 parts of metakaolin, 160 parts of medium sand with a modulus of 2.3-3.0, and 55 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 3 minutes to obtain a dry mix;

[0067] S301. According to weight, 5.5 parts of polycarboxylic acid high-efficiency water reducing agent and 150 parts of water are added to the dry mix and stirred for 2 minutes to form a slurry. Then, 50 parts of fly ash floating beads, 650 parts of modified lightweight coarse aggregate, and 15 parts of alkali-resistant chopped glass fibers are added and stirred for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0068] Example 2

[0069] S101. Add PI 52.5 silicate cement, ultrafine glass powder, water-based polyurethane dispersion, and silica sol into a stirring container in a mass ratio of 10:10:10:1, add water and stir until a thin elastic slurry with a fluidity of 250 mm is obtained, then add ceramsite made from high-aluminum fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure. Treat for 120 seconds, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, and sieve out the ceramsite with a sieve, and dry it naturally for more than 24 hours. During the natural drying, rotate the storage barrel once every 2 hours, and each rotation time is 5 minutes to prevent the ceramsite from sticking; so that a first elastic interface is formed on the surface of the ceramsite;

[0070] S102. PI 52.5R silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate are added to a stirring container in a mass ratio of 10:30:2:2, and water is added to stir until a thin slurry with a fluidity of 130 mm is obtained. Then, the ceramsite adsorbed on the first interface is added to the stirring container, and slowly stirred to allow the slurry to hang on the surface of the ceramsite to form a second interface.

[0071] S103. Use a cylindrical filter to automatically screen out the slurry-hanging ceramsite, and after natural solidification for 3 hours, send it into a rotating drum, separate the bonded ceramsite by rotation, and pile it on the site for natural curing after 12 hours. Wet it once every 3 days for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm;

[0072] S201. According to parts by weight, 340 parts of PO 42.5 ordinary Portland cement, 100 parts of PO 52.5 ordinary Portland cement, 50 parts of fly ash, 30 parts of silica fume, 10 parts of metakaolin, 150 parts of medium sand with a modulus of 2.3-3.0, and 50 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 5 minutes to obtain a dry mix;

[0073] S301. According to weight, 6 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water are added to the dry mix and stirred for 3 minutes to form a slurry. Then, 100 parts of fly ash floating beads, 600 parts of modified lightweight coarse aggregate, and 20 parts of alkali-resistant chopped glass fibers are added and stirred for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0074] Example 3

[0075] S201. According to parts by weight, 320 parts of PO 42.5 ordinary Portland cement, 100 parts of PO 52.5 ordinary Portland cement, 30 parts of fly ash, 20 parts of silica fume, 5 parts of metakaolin, 160 parts of medium sand with a modulus of 2.3-3.0, and 60 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 5 minutes to obtain a dry mix;

[0076] S301. According to weight parts, 5 parts of polycarboxylic acid high-efficiency water reducing agent and 145 parts of water are added to the dry mix and stirred for 2 minutes to form a slurry, and then 100 parts of fly ash floating beads, 700 parts of modified lightweight coarse aggregate prepared in Example 1, and 20 parts of alkali-resistant chopped glass fibers are added and stirred for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0077] Example 4

[0078] S201. According to parts by weight, 340 parts of PO 42.5 ordinary Portland cement, 120 parts of PO 52.5 ordinary Portland cement, 50 parts of fly ash, 30 parts of silica fume, 10 parts of metakaolin, 150 parts of medium sand with a modulus of 2.3-3.0, and 60 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 3 minutes to obtain a dry mix;

[0079] S301. According to weight parts, 7 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water are added to the dry mix and stirred for 3 minutes to form a slurry, and then 100 parts of fly ash floating beads, 650 parts of modified lightweight coarse aggregate prepared in Example 2, and 15 parts of alkali-resistant chopped glass fibers are added and stirred for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0080] Comparative Example 1

[0081] S201. According to parts by weight, 320 parts of PO 42.5 ordinary Portland cement, 100 parts of PO 52.5 ordinary Portland cement, 30 parts of fly ash, 20 parts of silica fume, 5 parts of metakaolin, 160 parts of medium sand with a modulus of 2.3-3.0, and 60 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 5 minutes to obtain a dry mix;

[0082] S301. According to weight, add 5 parts of polycarboxylic acid high-efficiency water reducing agent and 155 parts of water to the dry mix and stir for 2 minutes to form a slurry. Then add 100 parts of fly ash floating beads, 700 parts of ceramsite fired with high-alumina fly ash as the main raw materials (pre-sprayed with water and soaked), and 20 parts of alkali-resistant chopped glass fibers, stir for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0083] The ceramsite made from high-alumina fly ash as the main raw material was used directly without modification. At the same time, the amount of water was appropriately increased because the ceramsite absorbs water. Through the test of concrete, the compressive strength and flexural strength of the final concrete were significantly reduced due to the poor compressive strength and brittleness of the ceramsite.

[0084] Comparative Example 2

[0085] S201. According to parts by weight, 320 parts of unground PO 42.5 ordinary Portland cement, 100 parts of PO 52.5 ordinary Portland cement, 30 parts of fly ash, 20 parts of silica fume, 5 parts of metakaolin, 160 parts of medium sand with a modulus of 2.3-3.0, and 60 parts of fine sand with a modulus of 1.6-2.2 were added to a horizontal stirring device and stirred for 5 minutes to obtain a dry mix;

[0086] S301. According to weight, 5 parts of polycarboxylic acid high-efficiency water reducing agent and 145 parts of water are added to the dry mix and stirred for 2 minutes to form a slurry. Then, 100 parts of fly ash floating beads, 700 parts of modified lightweight coarse aggregate, and 20 parts of alkali-resistant chopped glass fibers are added and stirred for 5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

[0087] The preparation was carried out according to the technical scheme of Example 3, except that: PO 42.5 ordinary Portland cement was not ground, and its D80 particle size was 30-45 μm. The early strength was relatively low, which was not conducive to demolding.

[0088] Comparative Example 3

[0089] The modified lightweight coarse aggregate was prepared according to the technical solution of Example 1, except that the modified lightweight coarse aggregate was not subjected to the first interface treatment of step S101, and the ceramsite was directly treated in step S102. The obtained modified lightweight coarse aggregate had limited improvement in compressive strength and elasticity, especially reduced toughness of ceramsite, which was easily fractured when used in concrete under pressure, and reduced flexural performance.

[0090] 1. Early performance test of concrete of Examples 1-4 and Comparative Examples 1-3:

[0091] (1) Slump:

[0092] The slump is tested with reference to the standard GB / T 50080-2016 "Standard for Test Methods of Ordinary Concrete Mixtures". A trumpet-shaped slump bucket with an upper diameter of 100mm, a lower diameter of 200mm, and a height of 300mm is used. The concrete is filled three times. After each filling, the bucket wall is evenly hit from the outside to the inside for 25 times with a tamping hammer. After tamping, it is smoothed. Then the bucket is pulled up, and the concrete collapses due to its own weight. The height of the highest point of the concrete after collapse is subtracted from the bucket height of 300mm, and the slump is recorded as (mm). The data is shown in Table 1. It measures the fluidity, workability, and pumpability of concrete. Concrete with a higher slump is denser after solidification.

[0093] (2) 8h early strength:

[0094] Concrete samples were made according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The sample size was 150mm×150mm×100mm, and the compressive strength of concrete was tested for 8h. The test data is shown in Table 1. The demolding performance is measured by early strength to meet the needs of rapid production of prefabricated building concrete components.

[0095] Table 1 Early performance data of concrete of Examples 1-4 and Comparative Examples 1-3

[0096]

[0097] II. Late performance test of concrete of Examples 1-4 and Comparative Examples 1-3:

[0098] (1) Dry apparent density:

[0099] The dry apparent density of concrete was tested with reference to the relevant test methods in standard JGJ / T 12-2019 "Technical Standard for Application of Lightweight Aggregate Concrete". The test data are shown in Table 2.

[0100] (2) Concrete strength performance:

[0101] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", concrete samples were made and cured, and the compressive strength, tensile strength and flexural strength of concrete were tested. The test data are shown in Table 2.

[0102] The cross-sectional dimensions of the compressive strength specimen are 150mm×150mm×100mm, and the load loading speed is 0.8MPa / s.

[0103] The cross-sectional dimensions of the tensile strength specimen are 100 mm × 100 mm, and the load loading speed is 0.1 MPa / s.

[0104] The size of the flexural strength specimen is 150mm×150mm×600mm, and the load loading speed is 0.1MPa / s.

[0105] Table 2 Later performance data of concrete of Examples 1-4 and Comparative Examples 1-3

[0106]

[0107] Obviously, the lightweight reinforced concrete for prefabricated buildings prepared by the technical solution of the present invention has good early strength through reasonable cement grading and admixtures; through the toughening and strengthening improvement of expanded clay, while being lightweight, the concrete has good slump, good workability, stable pumping, and can form uniform and dense concrete, and the concrete has excellent compressive strength and flexural properties.

[0108] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, any modifications and equivalent substitutions made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lightweight reinforced concrete for prefabricated buildings, the lightweight reinforced concrete comprising the following raw material components by weight: 320-340 parts of PO 42.5 ordinary Portland cement, 100-120 parts of PO 52.5 ordinary Portland cement, 30-50 parts of fly ash, 20-30 parts of silica fume, 5-10 parts of metakaolin, 200-220 parts of fine aggregate, 50-100 parts of fly ash floating beads, 600-700 parts of modified lightweight coarse aggregate, 5-7 parts of polycarboxylate high-efficiency water reducing agent, 15-20 parts of reinforcing fiber, and 145-160 parts of water; wherein: The PO 42.5 ordinary Portland cement is ground to a D80 particle size of 5-15 μm; The particle size of the PO 52.5 ordinary Portland cement D80 is 30-45 μm; The surface of the modified lightweight coarse aggregate is a two-layer modified interface, including a first interface with elasticity and a second interface with compactness; the modified lightweight coarse aggregate is prepared by the following method: (1) Add silicate cement, ultrafine glass powder, water-based polyurethane dispersion and silica sol in a mass ratio of 10: (10-15): (5-10): (0.8-1) into a stirring container, add water and stir until a thin elastic slurry with a fluidity of 200-250 mm is obtained, then add ceramsite made from high-alumina fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, sieve out the ceramsite with a sieve, and dry naturally for more than 24 hours, so that a first elastic interface is formed on the surface of the ceramsite; (2) adding silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate into a mixing container in a mass ratio of 10: (25-30): (1-2): (2-3), adding water and stirring until a thin slurry with a fluidity of 130-150 mm is obtained, and then adding the ceramsite adsorbed on the first interface into the mixing container and stirring slowly to allow the slurry to adhere to the surface of the ceramsite to form a second interface; (3) Use a cylindrical filter to automatically screen out the slurry-covered expanded clay, and after natural solidification for 3 hours, send it into a rotating drum to separate the bonded expanded clay by rotation. After 12 hours, pile it on the site and water it for natural curing. Wet it once every 3 days and cure it for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm.

2. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized in that: The weight ratio of the PO 42.5 ordinary Portland cement to the PO 52.5 ordinary Portland cement is 3:

1.

3. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized in that: The water-cement ratio of the lightweight reinforced concrete is controlled at 0.32-0.

35.

4. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The particle size of the fly ash D80 is less than 10 μm; the particle size of the silica ash D80 is less than 3 μm; the particle size of the metakaolin is less than 10 μm; the particle size of the fly ash floating beads is 100-200 μm, and the bulk density is 720-750 kg / m 3 .

5. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The fine aggregate is a mixture of medium sand with a modulus of 2.3-3.0 and fine sand with a modulus of 1.6-2.2 in a mass ratio of 3:1; the mud content of the fine aggregate is less than 1%.

6. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The reinforcing fibers are alkali-resistant chopped glass fibers with a fiber diameter of 13-60 μm and a fiber length of 15-20 mm.

7. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The silicate cement used for preparing the modified lightweight coarse aggregate is at least one of PI 52.5, PI 52.5R, PI 62.5 and PI 62.5R.

8. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The ultrafine glass powder used to prepare the modified lightweight coarse aggregate is selected to have a particle size of less than 20 μm; the particle size of the basalt fine sand used is in the range of 0.1-0.2 mm; the magnesium oxide used is a medium powder with a particle size of 10-100 μm; and the particle size of the amorphous calcium aluminate used is in the range of 10-20 μm.

9. The lightweight reinforced concrete for prefabricated buildings according to claim 1 is characterized by: The aqueous polyurethane dispersion used for preparing the modified lightweight coarse aggregate is selected from one of anionic aliphatic polyurethane dispersion and anionic aromatic polyurethane dispersion.

10. The method for preparing the lightweight reinforced concrete for prefabricated buildings according to any one of claims 1 to 9, wherein the specific scheme is as follows: S101. Add silicate cement, ultrafine glass powder, water-based polyurethane dispersion, and silica sol into a stirring container in a mass ratio of 10: (10-15): (5-10): (0.8-1), add water and stir to adjust the fluidity to a thin elastic slurry in the range of 200-250 mm, then add ceramsite made from high-aluminum fly ash as the main raw material into the stirring container, slowly stir to soak the ceramsite, and evacuate the container to form a negative pressure, so that the slurry fully penetrates the through gaps on the surface of the ceramsite, sieve out the ceramsite with a sieve, and dry it naturally for more than 24 hours, so that a first elastic interface is formed on the surface of the ceramsite; S102. Add silicate cement, basalt fine sand, magnesium oxide, and amorphous calcium aluminate in a mass ratio of 10: (25-30): (1-2): (2-3) into a stirring container, add water and stir until a thin slurry with a fluidity of 130-150 mm is obtained, and then add the ceramsite adsorbed on the first interface into the stirring container and stir slowly to allow the slurry to adhere to the surface of the ceramsite to form a second interface; S103. Use a cylindrical filter to automatically screen out the slurry-hanging ceramsite, and after natural solidification for 3 hours, send it into a rotating drum, separate the bonded ceramsite by rotation, and pile it on the site for natural curing after 12 hours. Wet it once every 3 days for more than 30 days to obtain a modified lightweight coarse aggregate with a particle size of 8-12 mm; S201. Add PO 42.5 ordinary Portland cement, PO 52.5 ordinary Portland cement, fly ash, silica fume, metakaolin, and fine aggregate into a horizontal stirring device and stir for 3-5 minutes to obtain a dry mix; S301. Add polycarboxylic acid high-efficiency water reducing agent and water to the dry mix and stir for 2-3 minutes to form a slurry. Then add fly ash floating beads, modified lightweight coarse aggregate and reinforcing fiber and stir for 3-5 minutes to obtain lightweight reinforced concrete for prefabricated buildings.

Citation Information

Patent Citations

  • Lightweight high-strength ceramsite concrete as well as preparation method and application thereof

    CN110776289A

  • Recycled aggregate surface strengthening modifier and modification method thereof

    CN111777351A